Normative reference values, determinants and regression equations for the incremental shuttle walk test (ISWT) in healthy Asian population aged 21 to 80 years. - Muhammad Zulhaziq Bin Azman; Katherin S Huang; Wei Jun Koh; Sarah S Leong; Benjamin Ong; Johanna L Soon; Sherman W Tan; Melissa Y Chan; Mingxing Yang; Meredith T Yeung (PLoS ONE, 2023)
Background The validated Incremental Shuttle Walk Test (ISWT) is widely used for evaluating maximal exercise capacity, with the distance-walked (IWSD) as the primary outcome. However, there are no normative reference values (NRV) and reference equations to predict ISWD for the Singaporean population. Objectives This study aims to establish the NRV and reference equations for ISWD in healthy Singaporeans aged 21 to 80 and investigate the determining variables during ISWT. Methods This cross-sectional study recruited community-dwelling healthy subjects aged 21-80 from the community via convenience sampling. Each subject completed two trials of the ISWT according to the standard protocol. Variables measured during the trials included ISWD, pre-and post-test heart rate (HR), oxygen saturation, blood pressure (BP), modified Borg's dyspnoea score and Borg's rate of perceived exertion (RPE). Results 199 healthy Singaporean (females = 114, males = 85) participated in the study. The overall median ISWD was 660.0 metres (m) [interquartile range (IQR):440.0-850.0]. The age-stratified mean ISWD ranged from 430.0 m (IQR:350.0-450.0) (aged 60-80) to 480.0 m (IQR:438.0-650.0) (aged 40-59) to 780.0 m (IQR:670.0-960.0) (aged 21-39). Gender, age, weight, height and HR change (highest post-test HR minus pre-test HR) were the most significant variables (p < 0.001). IWSD (m) = 651.4(Height, m) +89.7(Gender, male = 1; female = 0) -6.31(Age, years) -3.61(Weight, kilograms) +2.54(HR change, beats per minute); R2 = 0.741. Previously published ISWT reference equations cannot accurately predict the ISWD in the Singaporean population. Conclusions This study investigated the ISWD NRV and established reference equations for healthy Singaporeans aged 21-80. The information would be beneficial in setting performance benchmarks to guide physical assessment, intervention and rehabilitation.